AKTIVITAS KOMUNIKASI CUSTOMER RELATIONS DALAM LAYANAN PENGEMUDI GOJEK SRIKANDI TERHADAP PENGGUNA JASA - Novilah, Novilah (Jurnal Visi Komunikasi, 2017)
The role of the driver GO-JEK considered important for PT. GO-JEK Indonesia, a company engaged in the field of online-based transportation services oriented to the satisfaction of its customers (customer). Including category GO-JEK female driver by the term Heroine. The driver is equipped with SOP of communication with the customer. The purpose of this study was to determine the GO-JEK Heroine driver's communication activities in the framework of customer relations. The results of this study is that the study concluded that the driver GO-JEK Heroine understand the importance of customer relations and excellent service for providing transportation services in accordance with the SOP (Standard Operating Procedure). Communication activities carried out, is motivated by the need to dig up information about the customer early done by the driver GO-JEK Heroine with customers. A second communication when meeting customers, assuring customer data in accordance with the reservation. Further, when serving customers both to drive customers (Go-Ride), Booking foods (Go-Food), reservations are shopping (Go-Mart) or Shipping (Go Send). The Driver GO-JEK Heroine talks when necessary and when deemed necessary. This is done in the process of serving maximally and improve the security of the driver her-self. Peran para pengemudi GO-JEK Srikandi dianggap penting bagi PT. GOJEK Indonesia, perusahaan yang bergerak di bidang jasa transportasi berbasis online yang berorientasi kepada kepuasan pelangganya (customer). Penelitian ini ditujukan untuk mengetahui aktivitas komunikasi pengemudi GO-JEK Srikandi dengan pelanggan dengan menggunakan landasan teori Kepuasan Pelanggan (Customer Satisfactions). Hasil penelitian terbagi dalam dua subbab yaitu: 1) Menggali informasi awal tentang customer yang dilakukan oleh para pengemudi GO-JEK Srikandi dengan pelanggan, 2) Aktivitas komunikasi para pengemudi GO-JEK Srikandi dalam melayani pelanggan meliputi 3 faktor: mengawali komunikasi saat bertemu pelanggan, saat melayani pelanggan yang dilakukan oleh para pengemudi GO-JEK Srikandi dan setelah melayani pelanggan yang dilakukan oleh para pengemudi GO-JEK Srikandi. Penelitian ini menyimpulkan dalam mencapai layanan prima dan melayani dengan secara memuaskan, driver GO-JEK Srikandi mengerti akan pentingnya SOP (Standart Operating Procedure) yang telah ditentukan PT. GO-JEK Indonesia.